Identifying thermal and pH stability of thiols compound in garlic extract - Samsudin, S.J. (Trans Tech Publications Ltd, 2014)
Thiosulfinates are a major compound found in most allium plant. Garlic, an allium species shows its potential to inhibit microbial and enzyme activity. The usage of garlic is widely known especially in the agriculture field. Thiosulfinates are formed by reaction of alliinase enzyme from their respective S-alk(en)yl cysteine sulfoxide after the crushing process of the garlic cloves. The stability of the garlic extract has been tested at variations of temperatures and pH values at different incubation time in terms of concentration (mM). After consecutive 4 hour incubation, thiols show higher concentration at temperature 30-35°C. The minimum concentration shows 22 reduction from the original thiols reading. Meanwhile, pH values of 2 (acidic) at 35°C gives higher thiols concentration compared to other conditions. © 2014 Trans Tech Publications, Switzerland.